Adjunctive therapy for glucose control in patients with type 1 diabetes - Harris K (Diabetes, Metabolic Syndrome and Obesity : Targets and Therapy, 2018)
Kira Harris,1,2 Cassie Boland,1,3 Lisa Meade,1,4 Dawn Battise1,5 1Pharmacy Practice Faculty, Wingate University School of Pharmacy, Wingate, NC, USA; 2Clinical Pharmacy Specialist – Novant Health Family Medicine Residency Program, Cornelius, NC, USA; 3Clinical Pharmacy Specialist – Novant Health Cotswold Family Medicine – Arboretum, Charlotte, NC, USA; 4Clinical Pharmacy Specialist – Piedmont HealthCare Endocrinology, Statesville, NC, USA; 5Clinical Pharmacy Specialist – Cabarrus Family Medicine – Harrisburg, Harrisburg, NC, USA Abstract: Type 1 diabetes mellitus (T1DM) is characterized by relative or absolute insulin deficiency. Despite treatment with insulin therapy, glycemic goals are not always met, and insulin therapy is sometimes limited by adverse effects, including hypoglycemia and weight gain. Several adjunctive therapies have been evaluated in combination with insulin in patients with T1DM to improve glycemic control while minimizing adverse effects. Pramlintide, an amylin analog, can improve glycemic control, primarily through lowering postprandial blood glucose levels. Patients may experience weight loss and an increased risk of hypoglycemia and require additional mealtime injections. Metformin provides an inexpensive, oral treatment option and may reduce blood glucose, especially in overweight or obese patients with minimal risk of hypoglycemia. Metformin may be more effective in patients with impaired insulin sensitivity. Glucagon-like peptide-1 receptor agonists reduce primarily postprandial blood glucose and insulin dose and promote weight loss. They are expensive, cause transient nausea, may increase risk of hypoglycemia and require additional injections. Sodium–glucose transport-2 inhibitors improve glycemic control, promote weight loss and have low risk of hypoglycemia with appropriate insulin adjustment; however, these agents may increase the risk of diabetic ketoacidosis in patients with T1DM. Patient-specific characteristics should be considered when selecting adjunctive therapy for patients with T1DM. Close monitoring, insulin dose adjustments and patient education are all important to ensure safe and effective use of these agents. Keywords: type 1 diabetes mellitus, metformin, amylin, sodium–glucose cotransporter 2 inhibitors, glucagon-like peptide-1 receptor agonists, dipeptidyl-peptidase 4 inhibitors